A novel virotherapy encoding human interleukin-7 improves ex vivo T lymphocyte functions in immunosuppressed patients with septic shock and critically ill COVID-19 - Crausaz, Morgane; Monneret, Guillaume; Conti, Filippo; Lukaszewicz, Anne-Claire; Marchand, Jean-Baptiste; Martin, Perrine; Inchauspé, Geneviève; Venet, Fabienne (Frontiers in Immunology, 2022)
A majority of septic patients surviving the first days in intensive care units (ICU) enter a state of immunosuppression contributing to their worsening. A novel virotherapy based on the non-propagative Modified Virus Ankara (MVA) expressing the human IL-7 (hIL-7) cytokine fused to an Fc fragment, MVA-hIL-7-Fc, was developed and shown to enhance innate and adaptive immunity and confer survival advantages in murine sepsis models. Here, we assessed the capacity of hIL-7-Fc produced by the MVA-hIL-7-Fc to improve ex vivo T lymphocyte functions from ICU septic patients. Primary hepatocytes were transduced with the MVA-hIL-7-Fc or an empty MVA and cell supernatants containing the secreted hIL-7-Fc were harvested for in vitro and ex vivo studies. Whole blood from ICU patients (septic shock = 15, COVID-19 = 30) and healthy donors (n = 36) was collected. STAT5 phosphorylation, cytokine production and cell proliferation were assessed upon TCR stimulation in presence of MVA-hIL-7-Fc infected cell supernatants. Cells infected by MVA-hIL-7-Fc produced a dimeric, glycosylated and biologically active hIL-7-Fc. Cell supernatants containing the expressed hIL-7-Fc triggered the IL-7 pathway in T lymphocytes as evidenced by the increased STAT5 phosphorylation in CD3+ cells from patients and healthy donors. The secreted hIL-7-Fc improved IFN-γ and/or TNF-α productions and CD4+ and CD8+ T lymphocyte proliferation after TCR stimulation in patients with bacterial and viral sepsis. This study demonstrates the capacity of the novel MVA-hIL-7-Fc-based virotherapy to restore ex vivo T cells immune functions in sepsis and COVID-19 ICU patients further supporting its clinical development.